Childhood Anemia and Risk for Acute Respiratory Infection, Gastroenteritis, and Urinary Tract Infection: A Systematic Review - Jayamanna, Ushani; Jayaweera, J. A. A. Sampath (Journal of Pediatric Infectious Diseases, 2022)
Objective Children younger than 5 years, particularly children below 2 years, are among the most vulnerable groups for developing anemia and infections. This review is intended to assess the association between anemia and childhood acute respiratory infections (ARTIs), acute gastroenteritis (AGE), and urinary tract infections (UTIs).Methods PubMed was searched for published articles from January 2000 to August 2021 in English using the following terms: anemia and acute respiratory tract infections in children; anemia and UTIs in children; anemia and AGE in children. The data extraction were conducted by two investigators using the same methodology. Using descriptive statistics, the data from different sources were synthesized, including medians and ranges.Results A total of 426 articles and 27 original articles and 1 systematic review were included. Iron deficiency anemia is common among children between 6 months and 3 years of age. This age group can be considered a highly susceptible age for contraction of ARTI and AGE. Children below 5 years suffer five to six episodes of acute ARTI per year on average, and pneumonia accounts for the highest number of deaths, which is around 1.1 million each year. When considered, the odds ratio of anemia to increase the susceptibility of contracting lower ARTI would range from 2 to 5.7. Also, anemic children were 10 times more susceptible to developing acute recurrent ARTI and 4 times more susceptible to contracting pneumonia. Respiratory syncytial virus is the commonest viral etiology. Anemia would increase the risk of diarrhea by 2.9-fold in toddlers, while mild anemia, moderate anemia, and severe anemia would increase the susceptibility to contract AGE by 1.6, 1.6, and 8.9 times, respectively. Rotavirus is the commonest etiology. Some studies observed a protective effect of mild to moderate iron-deficient anemia from respiratory infections.Conclusion Infectious disease imposes a heavy burden on the health sector in a country. The highest susceptibility for infections and the development of anemia would be due to inadequate nutrition supplementation to meet the demand during rapid body growth. Therefore, based on the available evidence, one can take the necessary steps to reduce the infectious disease burden by correcting the anemia status in children.
Keywords: anemia; children; ARTI; AGE; UTI and risk for infections